Avian pest control in vineyards is driven by interactions between bird functional diversity and landscape heterogeneity. Issue 2 (25th July 2016) - Barbaro, Luc; Rusch, Adrien; Muiruri, Evalyne W.; Gravellier, Bastien; Thiery, Denis; Castagneyrol, Bastien
Summary: Insectivorous birds are increasingly recognized for the crucial pest control services they provide to agroecosystems. While both the foraging activity and functional diversity of birds are enhanced by multiscale habitat heterogeneity, little is known about how these relationships may influence avian top‐down control of insects. Specifically, interactive effects of bird community structure and habitat heterogeneity on pest control across spatial scales have rarely been explored. We sampled bird communities and measured avian predation on plasticine model prey, as a proxy for lepidopteran pest control, in 20 vineyards of south‐western France. Vineyards differed both in sward heterogeneity at the local scale and amount of surrounding semi‐natural habitats at the landscape scale. Functional diversity metrics and community‐weighted mean traits were computed for bird communities based on a species–trait table including diet, foraging method, nesting site, migration strategy, laying date, home range size, clutch size and body mass. We used mixed models to test for the interacting effects of habitat heterogeneity and bird functional diversity on avian predation rates of plasticine prey. Contrary to expectations, bird functional diversity decreased with landscape‐scale heterogeneity, but was higher in vineyards managed with heterogeneous sward structures. In contrast, foliage‐gleaning insectivores were more abundant in landscapes supporting more semi‐natural habitats, suggesting an increase in their contribution to pest control along the landscape heterogeneity gradient. Accordingly, we found that avian predation on plasticine prey increased with bird functional evenness both in more heterogeneous vineyards at the local scale and in landscape mosaics supporting more semi‐natural habitats. Synthesis and applications . Our study demonstrates that habitat heterogeneity at both local and landscape scales influenced avian insectivory in vineyard agroecosystems by interacting with bird community structure. It provides important insights for ecological intensification in vineyards, pointing out that management options need to be adapted to both the functional composition of local bird communities and landscape context. We suggest that both on‐field and off‐field management can be used to enhance natural pest control services provided by birds in vineyards, especially by favouring sward heterogeneity and patches of semi‐natural habitats within large vineyard stands at the landscape scale.